Case report on Arrhythmogenic Right Ventricular Dysplasia - Rabbani, Safia Binte; Ahmed, Mir Nesaruddin; Malik, Fazilatunnesa; Rana, Rubina Afroz; Chowdhury, Md Shamim (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Arrhythmogenic cardiomyopathy (AC) is a genetic disease characterized by fibro-fatty replacement of either ventricles in isolation or in combination. It may cause tachyarrhythmias to sudden cardiac death, especially in young adult. When ventricular tachycardia (VT) is the principal manifestation then the condition is termed as arrhythmogenic right ventricular dysplasia (ARVD). Here we present a case of ARVD in a 36 years old hypertensive male who presented with sudden onset of chest tightness, palpitations, breathing difficulty, dizziness for 20 minutes. In emergency department his electrocardiogram (ECG) showed sustained VT. After 200 joule DC cardioversion he was reverted to sinus rhythm, then resting ECG showed T-wave inversion (TWI) in V1-V3 along with epsilon wave. His echocardiogram also revealed dilated right ventricle (RV) along with hypertrabeculation, RV wall motion abnormality and low RV ejection fraction (EF), his coronaries were normal on coronary angiogram (CAG). He was discharged from the hospital after Implantable Cardioverter Defibrilator (ICD) implantation with beta-blocker and advised to restrict excessive physical activity. J Bangladesh Coll Phys Surg 2024; 42: 86-91